Best Answer

a^2+b^2=c^2

a^2=c^2-b^2

a=(c^2-b^2)^(1/2)

More answers

You add c squared and b squared together to get a squared. This is based on the Pythagorean theorem, which states that in a right triangle, the square of the hypotenuse (a) is equal to the sum of the squares of the other two sides (b and c).

Q: What do you do with c squared and b squared to get a squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Educational Theory

The musical notes are A, B, C, D, E, F, and G. Each note represents a specific pitch in music. These notes can be combined in various patterns to create melodies and harmonies.

When you subtract 7x^2 from 5x^2, you get -2x^2.

a,b,c,d are numbers of which atleast one is non zero such that a+b+c+d=0 let p=ab+bc+cd prove that one of 19p+99q and 19q+99p must be negative

A 2.48 typically translates to a C+. However, grading scales can vary depending on the institution.

To achieve a 3.0 GPA with 6 classes, you would need to earn a total of 18 grade points. This could be achieved by earning a mix of B grades (3.0 grade points) and B+ grades (3.3 grade points) across all 6 classes.

Related questions

he made the theorem C squared = A squared + B squared and A squared = C squared - B squared or B squared = C squared - A squared

B squared equals c squared minus a squared then to find B take the square root of you answer for b squared

a(squared)+b(squared)=c(squared) The largest number is the c, and you can choose the a and b, since you need to find the a or the b. For example: You have the numbers 3, and 5 and you needed to find b. a(squared+b(squared)=c(squared) 3(squared)+b(squared)=5(squared) 9+b(squared)=25 -9 -9 b(squared)=16 Then take the square root b=4

if you mean a right triangle then the formula is a squared + b squared = c squared. a and b are the legs and c is the hypotunese. the legs are the smallest number then the hypotenese. An example is a=3 , b= ? and c =5 use the formula : a squared + b squared = c squared 3 squared + b squared = 5 squared 9 + b squared = 25 -9 - 9 _________________________________________ b squared = 16 Then you have to take the squared root of 16 which is 4 and 4 is b squared.

4

a squared + b squared = c squared a=leg b=leg c=hypotenuse

it is asquared +b squared = c squared

The Pythagoream Thereom is a^2 + b^2 = c^2. Written out it is a squared plus b squared equals c squared.

c= sq rt of 73

A squared + B squared = C squared

a squared + b squared = c squared

a squared + b squared = c squared